(untitled) (Research, Society and Development, 2022)
In December 2019, a new Coronavirus disease called COVID-19, broke out in China, expanding across the world evolving into a worrying pandemic. According to the Ministry of Health, until May 31, 2022, there were 30.977.661 cases of COVID-19 in Brazil and approximately 666.516 deaths were recorded. The pandemic has caused important consequences in all sectors such as high unemployment rates, economy, education, and health, bringing a chronic underfunding of the Unified Health System (SUS), generating an unprecedented health crisis. COVID-19 is a disease caused by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2). Symptoms of SARS-CoV-2 infection can include fever, cough, loss of smell and taste, sore throat, headache, diarrhea and fatigue, which can vary from person to person, however, most infected people can remain asymptomatic or develop mild to moderate symptoms, without the need for hospital intervention. However, some individuals can progress from severe pneumonia to respiratory failure, septic shock, and possibly death. In this study, we report a case of a 42-year-old Brazilian woman diagnosed with Multiple Sclerosis (MS) after COVID-19 infection, alerting to the association of post-COVID-19 MS. Although the mechanism of the relationship between MS and COVID-19 is not studied here, the study highlights this possibility and the importance of investigating symptoms such as paresthesias, muscle weakness and visual symptoms after SARS-CoV-2 infection.